2010
DOI: 10.2147/ijn.s8719
|View full text |Cite
|
Sign up to set email alerts
|

Targeted drug delivery into reversibly injured myocardium with silica nanoparticles: surface functionalization,  natural biodistribution, and acute toxicity

Abstract: Abstract:The clinical outcome of patients with ischemic heart disease can be significantly improved with the implementation of targeted drug delivery into the ischemic myocardium. In this paper, we present our original findings relevant to the problem of therapeutic heart targeting with use of nanoparticles. Experimental approaches included fabrication of carbon and silica nanoparticles, their characterization and surface modification. The acute hemodynamic effects of nanoparticle formulation as well as nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 10 publications
(9 reference statements)
0
34
0
1
Order By: Relevance
“…The liver was chosen for sampling and analysis on the basis of previous biodistribution experiments showing maximal accumulation of silica in this organ. 12 Quantitative analysis of silicon content within the samples was performed using atomic absorption spectroscopy. The product of mineralization obtained after drying was analyzed by atomic absorption spectrometry with electrothermic atomization and Zeeman correction.…”
Section: Biodegradation Of Silica Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver was chosen for sampling and analysis on the basis of previous biodistribution experiments showing maximal accumulation of silica in this organ. 12 Quantitative analysis of silicon content within the samples was performed using atomic absorption spectroscopy. The product of mineralization obtained after drying was analyzed by atomic absorption spectrometry with electrothermic atomization and Zeeman correction.…”
Section: Biodegradation Of Silica Nanoparticlesmentioning
confidence: 99%
“…We have previously shown that 6-13 nm silica nanoparticles are not toxic during acute intravenous administration and can also be readily functionalized by immobilization or chemical assembly approaches. 12 Although recent research has made signif icant strides in clarifying the mechanisms of endogenous and pharmacological cardioprotection, we still do not have an "ideal" cardioprotective agent with a favorable safety and efficacy profile. There is now considerable evidence for involvement of adenosine in the mechanism(s) of ischemic postconditioning-induced cardiac protection.…”
Section: Introductionmentioning
confidence: 99%
“…Their engulfment occurred without a need for surface activation by organic or polymeric groups, as previously reported for similar materials in other tissues. 9,10,20,[29][30][31] Uptake was likely mediated by the high affinity of phospholipids in the plasma membrane for particle surface groups, such as silanols and silanolate. 25,[32][33][34] The TEM images (Figures 2 and 3, and Figures S1 and S2) show that MCM41-cal and SBA15-cal are distributed in different cellular compartments and are abundant in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, the standard pyrogenic highly dispersed silica (Aerosil A380 mark obtained from Vekton, Russia) was used throughout experiments. Surface area of silica nanoparticles was determined with use of Brunauer-Emmett-Teller (BET) method and averaged from 170 to 380 m 2 /g (Galagudza et al, 2010). The mean particle diameter varied from 6 to 13 nm.…”
Section: Fabrication Characterization and Surface Modification Of Smentioning
confidence: 99%